The Bennett pinch for non-relativistic electrons. (December 2018) - Allen, J. E.; Simons, L.
Abstract : A theory of the Bennett pinch is presented for the case of non-relativistic electrons. In this way the basic physics of the phenomenon can be clearly demonstrated. The magnetic force acting on the electrons is transmitted to the positive ions via an electrostatic field.